Fremdsprachen an Wiener Grundschulen – Im Regelschulwesen und in aktuellen Schulversuchsmodellen - Seebauer, Renate (Revija za elementarno izobraževanje, 2015)
Foreign Languages in Vienna Primary Schools – in Mainstream Education and in Current Experimental Models. Starting with a short retrospective and an overview of the incorporation of foreign language learning into the Austrian curriculum for primary schools the paper in hand describes the current situation of foreign language teaching in primary schools as well as various current models of foreign language education in primary schools in Vienna (school year 1 to 4). In terms of objectives these models exceed the requirements of the curriculum of the formal education system or regard themselves as quantitative and qualitative enrichment. They follow different didactic approaches and/or site-specific characteristics and needs. The formulation of basic skills is to be understood as an attempt to find a common basis of output indicators and to facilitate the transition to secondary education. Although English is the most commonly chosen resp. offered language the paper also refers to school experiments that focus on Romance or Slavic languages or on languages of Austra’s neighbouring countries.